POTENSI PETANI IKAN DALAM MODIFIKASI MENU GIZI KELUARGA UNTUK MENCEGAH KEJADIAN STUNTING PADA BALITA DENGAN PENDEKATAN FTAD (FARMERS TEAM ACHIEVEMENT DIVISION) - Atikah Rahayu; Parida Rahmi; Lia Anggraini; M Anshori Rahman (Jurnal Abdimas Kesehatan (JAK), 2019)
The implication of a long malnutrition in baduta called stunting, the impact will experience growth barriers / height according to age and brain development so that there is a chance of losing the next generation (lost generation). This condition is likely to occur given the data from the Health Office, Banjar District is one of the largest contributors to short cases in South Kalimantan, and the largest case is found in the working area of Sungai alang puskesmas as much as 41.7% (2015) and Rahayu and Putri's research results in Sungai alang found that the majority of children under five experienced stunting of 62.7% or a total of 79 people. Ironically, this region is located on a riverbank, so the area should not be included in the category of areas with very poor public health problems with a stunting prevalence of ≥ 40%, because the local commodity produced ie the largest fish in South Kalimantan is 12,595.9 tons per year. Fish is one source of protein which is at the same time a macro nutrient that contributes energy to the body. Considering that the Alang River region is one of the areas located along the riverbanks and most of the residents' livelihoods are fish farmers, it is therefore necessary to educate these farmers so that the fish obtained are not only sold but utilized by processing fish food by modifying variants based on the menu local fish. One of the methods used so that the knowledge and skills of modifying local fish menus to farmers is effective, so the active learning method using the FTAD (Farmers Team Achievement Division) approach is used. The results of the activities showed that before giving education to farmers most of them had a level of knowledge of less than 63.3% and after providing education the knowledge of farmers increased to 76.7% had a level of knowledge of the category quite well. Based on statistical analysis it was stated that by providing education about modifying nutrition menus for families to prevent stunting in children meaningfully by using the FTAD (farmers team achievement division) approach.